Environmental drivers interactively affect individual tree growth across temperate European forests. (22nd November 2018) - Maes, Sybryn L.; Perring, Michael P.; Vanhellemont, Margot; Depauw, Leen; Van den Bulcke, Jan; Brūmelis, Guntis; Brunet, Jörg; Decocq, Guillaume; den Ouden, Jan; Härdtle, Werner; Hédl, Radim; Heinken, Thilo; et al.
Abstract: Forecasting the growth of tree species to future environmental changes requires a better understanding of its determinants. Tree growth is known to respond to global‐change drivers such as climate change or atmospheric deposition, as well as to local land‐use drivers such as forest management. Yet, large geographical scale studies examining interactive growth responses to multiple global‐change drivers are relatively scarce and rarely consider management effects. Here, we assessed the interactive effects of three global‐change drivers (temperature, precipitation and nitrogen deposition) on individual tree growth of three study species ( Quercus robur/petraea, Fagus sylvatica and Fraxinus excelsior) . We sampled trees along spatial environmental gradients across Europe and accounted for the effects of management for Quercus . We collected increment cores from 267 trees distributed over 151 plots in 19 forest regions and characterized their neighbouring environment to take into account potentially confounding factors such as tree size, competition, soil conditions and elevation. We demonstrate that growth responds interactively to global‐change drivers, with species‐specific sensitivities to the combined factors. Simultaneously high levels of precipitation and deposition benefited Fraxinus, but negatively affected Quercus' growth, highlighting species‐specific interactive tree growth responses to combined drivers. For Fagus, a stronger growth response to higher temperatures was found when precipitation was also higher, illustrating the potential negative effects of drought stress under warming for this species. Furthermore, we show that past forest management can modulate the effects of changing temperatures on Quercus' growth; individuals in plots with a coppicing history showed stronger growth responses to higher temperatures. Overall, our findings highlight how tree growth can be interactively determined by global‐change drivers, and how these growth responses might be modulated by past forest management. By showing future growth changes for scenarios of environmental change, we stress the importance of considering multiple drivers, including past management and their interactions, when predicting tree growth. Abstract : Tree growth responds to global‐change drivers such as climate change or atmospheric deposition and to local land‐use drivers such as forest management. Yet, large geographical‐scale studies examining interactive growth responses to multiple global‐change drivers are relatively scarce and rarely consider management effects. We assessed interactive effects of three global‐change drivers (temperature, precipitation and nitrogen deposition) on tree growth of three study species across Europe ( Quercus robur/petraea, Fagus sylvatica, Fraxinus excelsior ) and accounted for management effects for Quercus. We demonstrate that growth responds interactively to these drivers, with species‐specific sensitivities. Furthermore, past management modulated the effects of changing temperatures on Quercus' growth.